Conversion of Crude Glycerol from by-Product Biodiesel into Bio-additive of Fuel through Acetylation Reaction based on Modified Zeolite Catalyst - Dewajani, Heny; Zamrudy, Windi; Saroso, Hadi; Paramarta, Satria; Mulya, Wahyudianto (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2019)
Biodiesel is one of the alternative fuels produced from the transesterification reaction between triglycerides and alcohols with glycerol by-products. So far, the resulting crude glycerol has not been maximally utilized because of its low purity. So, it is necessary to purify glycerol before turning it into a more useful compound. The purified glycerol can be reacted with acetic acid within esterification reaction (acetylation process) using an acid catalyst to produce glycerol triacetate (triacetin). One of the uses of triacetin as an additive in gasoline and biodiesel. The purpose of this study is to utilize glycerol from by-products from biodiesel production to bio-additive materials that can improve fuel quality and are environmentally friendly. The method used in this study begins with the purification of crude glycerol, modification of zeolite catalyst with impregnated of nickel metal followed by an acetylation reaction which held on temperature of 100Â°C for 60 min. The experimental results are analyzed using base titration to determine the remaining unreacted acids and are applied as bio-additives by adding them to commercial fuels and measured the increasing octane numbers. The result shows that the reaction conversion increases with increasing mole ratio of reactants and catalysts with the best results in the mole ratio of acetic acid and glycerol is 9:1 and catalyst 5% by weight of acetic acid with a conversion of 66.02%. As bio-additives the reaction product could increase the octane number of commercial fuel by 6.5 up to 8.5%.Â Keywords: glycerol, acetylation reaction, mofified zeolite, bio-additive